Faktor-faktor Utama untuk Meningkatkan Kualitas Kerja Tim di Startup Indonesia menggunakan Kerangka aTWQ - Muhammad Fathin; Teguh Raharjo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Due to the ever-changing needs of IT in today's businesses, agile software development has become popular due to its adaptive capabilities. Startups are among those who continuously strive to meet changing needs. Despite the potential benefits of the Agile methodology, teamwork quality remains a challenge. Furthermore, the global recession has made it increasingly important for startups to have effective teamwork, given the high level of uncertainty that leads to challenges in surviving, especially with cost-cutting and downsizing efforts. Therefore, this study aims to evaluate teamwork quality in Indonesian startups using the Agile Teamwork Quality (aTWQ) approach. TWQ is a comprehensive set of criteria designed to assess teamwork quality in agile environments. The primary objective of this study is to identify the factors that most strongly increase the quality of teamwork of Indonesian startups. To achieve this objective, data will be collected from Indonesian companies using an online survey based on the aTWQ framework. The challenges were identified most on the dimensions of cohesion, balance of contribution, and effort. The findings of this study are consistent with previous research, which may hopefully help start-ups in Indonesia improve their teamwork quality and achieve greater success in their respective industries.